2020
DOI: 10.1177/0033294120909447
|View full text |Cite
|
Sign up to set email alerts
|

What Is “Normal” Infant Sleep? Why We Still Do Not Know

Abstract: The human need for sleep is universal and unquestioned; however, humans vary in their sleep needs according to age, individual differences, as well as cultural and social norms and practices. Therefore, what is “normal” in infant sleep and the development of sleep architecture in humans is highly dependent on biological and sociocultural variables as well as socially constructed assumptions about what infant sleep “should” look like. This paper uses a multidisciplinary approach to review papers from fields inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 163 publications
0
18
0
Order By: Relevance
“…Although highlighted safe sleep recommendations seem to be widely known and recommended, research shows that parents tend to form their own practice in their home environments [ 22 , 28 , 29 , 47 ]. This applies particularly to the sharing of the same bed surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although highlighted safe sleep recommendations seem to be widely known and recommended, research shows that parents tend to form their own practice in their home environments [ 22 , 28 , 29 , 47 ]. This applies particularly to the sharing of the same bed surface.…”
Section: Discussionmentioning
confidence: 99%
“…The thematic focus of the review is identified as complex, involving many environmental, parental, and child factors, in addition to relations between different participants [ 16 , 22 ]. While working on the study protocol, we decided to use a framework adapted from a well-known transactional model of infant sleep to guide data extraction from each study and summarize topics and factors [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In WEIRD societies models of infant care became biomedicalized as a consequence of the reliance on statistical normalcy, that is, conceptualized as within the purview of medical experts who set the standards for what is considered “normal” and “healthy” sleep (Ball, 2008; Ball et al, 2019; McKenna et al, 2007; Tomori, 2014). Biological and evolutionary views on infant sleep norms entered the discourse only over the past 20 years, but are now beginning to gain traction with both parents and health practitioners, and with a small but growing group of pediatricians and infant sleep researchers (e.g., Barry, 2020; Mileva‐Seitz et al, 2017). This approach seeks to root guidance for parents in data related to human infant physiology and evolutionary expectations, rather than cultural norms that have shifted enormously in the last two centuries.…”
Section: Conclusion: Establishing “Normalcy” For Infant Sleepmentioning
confidence: 99%
“…Pre‐natal fantasies of a baby sleeping soundly in his/her carefully prepared crib are rarely realized; yet unrealistic expectations are unintentionally reinforced by clinicians and well‐wishers; even strangers take an interest in whether new babies they encounter are “good,” (meaning sleeping “through the night”). The Western cultural obsession with infant sleep leads parents to wonder, sooner or later, whether their infant's sleep patterns are “normal,” what they could or should be doing differently, and whether something they are not doing (or buying) would help their baby to fall asleep more quickly, to sleep for longer, or more deeply, or through the night (Ball, 2020; Barry, 2020).…”
Section: Introductionmentioning
confidence: 99%